Discovery of a novel and selective fungicide that targets fungal cell wall to treat dermatomycoses: 1, 3‐bis(3, 4‐dichlorophenoxy)propan‐2‐aminium chloride. Issue 2 (15th December 2019) - Flores Dalla Lana, Daiane; Neiva Lavorato, Stefânia; Minussi Giuliani, Laura; Cruz, Letícia; Lopes, William; Henning Vainstein, Marilene; Camargo Fontana, Igor; Rigon Zimmer, Aline; de Araújo Freitas, Murillo; de Andrade, Saulo Fernandes; José Alves, Ricardo; Meneghello Fuentefria, Alexandre
Summary: Background: Fungal infections are highly prevalent and are responsible for high rates of morbidity and mortality. In this context, the search for new treatment alternatives is very relevant. Objectives: Analyse chemical compounds for antifungal potential against dermatomycosis fungi. Methods: The antifungal activity of 121 compounds, intermediates or derivatives of 1, 3‐bis(aryloxy)propane substituted at C‐2 (111 compounds) and isothiouronium derivatives (10 compounds) was investigated through susceptibility tests, mechanism of action, toxicity and hydrogel incorporation. Results: The compound 1, 3‐bis(3, 4‐dichlorophenoxy)propan‐2‐aminium chloride (2j ) was the most active fungicide against dermatophytes and Candida spp., at very low concentrations (0.39‐3.12 µg/mL), including action on resistant and multidrug‐resistant clinical strains. Compound 2j has presented a promising toxicity profile, showing selectivity index >10, relative to human lymphocytes. The compound was classified as non‐irritant by the HET‐CAM test and did not cause histopathological alterations in pig ear skin, thus presenting an excellent perspective for topical application. 2j targets the fungal cell wall, which was confirmed by scanning electron microscopy, which also indicated the additional ability of 2j to inhibit the Candida albicans pseudohyphae formation and biofilm of Microsporum canis . Compound 2j was incorporated in a hydrogel with bioadhesive potential. The results of the human skin permeation showed that 2j remained significantly in the epidermis, ideally for the dermatomycosis treatment. Conclusions: Therefore, the compound 2j demonstrated the potential for antifungal drug development, with a action mechanism elucidated and already applied in a semisolid formulation as a new therapeutic option for fungal skin infections. Abstract : Assignments for the promising antifungal molecule 2j .